(untitled) (Bangladesh Journal of Botany, 2026)
This study aims to document traditional knowledge related to medicinal plants used by local communities in the Relizane Province of Northwestern Algeria, with the dual objective of preserving cultural heritage and supporting the sustainable use and pharmacological potential of these resources. Ethnobotanical surveys were conducted in seven regions of Relizane, engaging 210 local informants. A total of 70 medicinal plant species, belonging to 32 families, were identified. The most frequently cited families were Lamiaceae, Apiaceae, and Asteraceae, with Thymus vulgaris, Matricaria chamomilla, and Mentha spicata emerging as the most commonly used species. Data were analyzed using ethnobotanical indices such as Use Value (UV) and Informant Consensus Factor (ICF). Thymus vulgaris had the highest UV (0.080), while the highest ICF values were observed for respiratory (0.80) and digestive disorders (0.72), indicating a high level of agreement among informants. In contrast, reproductive health exhibited the lowest ICF (0.25). Bangladesh J. Bot. 55(1): 77-84, 2026 (March)